A multi-objective optimisation of TIG welding parameters using response surface methodology. (14th April 2021) - Srivastava, Shekhar; Kumar, Sandeep; Garg, Rajiv Kumar
This study is aimed to examine the effect of different variables such as gas flow rate, travel speed and current for the welding of mild steel (IS: 2062) with TIG welding. In this study, an effect of the identified variables has been studied on bead width, bead height and penetration. Pilot experiments were performed to find the most effective levels of factors to be used for experimentation. Experimental runs have been designed using central composite design (CCD) technique and analysis has been done to inquest the action of different input parameters on output parameters quality characteristics. The selection of the range of input parameters was done on the basis of the size of the specimen. On the basis of experimental observation, the mathematical model has been formed using regression analysis through a statistical software. An attempt has been made to minimise the bead width and height and maximise the depth of penetration using response surface methodology.